A Study on People Perception of Digital India - Rekha, M; R. Shanthi, Dr. (International Journal of Engineering and Technology, 2018)
This primary research was conducted to explore the perception of Indian citizens with respect to the Government of India flagship program such as digital India initiative. This campaign was initiated by Honorable Prime Minister of India Shri. Narendra Modi Ji on July 2015. This program has three components namely digital literacy, digital infrastructure and digital economy. The present study was descriptive and analytical nature to examine the people perception with respect to digital India initiative. The result indicates that Indian citizens are poses higher awareness on digital India campaign and they are practicing in their day to day life for the betterment of India economy through digital transformation of the country.Â